Tumor Treating Fields With Gemcitabine and Nab-Paclitaxel for Locally Advanced Pancreatic Adenocarcinoma: Randomized, Open-Label, Pivotal Phase III PANOVA-3 Study - Babiker, Hani M; Picozzi, Vincent; Chandana, Sreenivasa R; Melichar, Bohuslav; Kasi, Anup; Gang, Jin; Gallego, Javier; Bullock, Andrea; Chunyi, Hao; Wyrwicz, Lucjan; Hitre, Erika; Osipov, Arsen; et al. (Journal of clinical oncology, 2025)
PURPOSE: Tumor treating fields (TTFields) use alternating electric fields to disrupt cancer cell proliferation. Feasibility of TTFields therapy with gemcitabine/nab-paclitaxel was previously demonstrated in patients with advanced pancreatic adenocarcinoma. PANOVA-3 was designed to confirm safety and efficacy of TTFields in patients with unresectable locally advanced pancreatic adenocarcinoma (LA-PAC). METHODS: In this global phase III trial, 571 patients with newly diagnosed LA-PAC were randomly assigned to receive gemcitabine 1,000 mg/m2 and nab-paclitaxel 125 mg/m2 by intravenous infusion once a day on days 1, 8, and 15 of a 28-day cycle with or without TTFields. The primary end point was overall survival (OS). Secondary end points included progression-free survival (PFS), local PFS, pain-free survival, and overall response rate (ORR). Distant PFS was analyzed post hoc. RESULTS: OS was significantly prolonged using TTFields with gemcitabine/nab-paclitaxel versus gemcitabine/nab-paclitaxel (median, 16.2 months [95% CI, 15.0 to 18.0] v 14.2 months [95% CI, 12.8 to 15.4]; hazard ratio [HR], 0.82 [95% CI, 0.68 to 0.99]; P = .039). PFS, local PFS, and ORR were not improved. Pain-free survival was significantly prolonged with TTFields with gemcitabine/nab-paclitaxel (median, 15.2 months [95% CI, 10.3 to 22.8] v 9.1 months [95% CI, 7.4 to 12.7]; HR, 0.74 [95% CI, 0.56 to 0.97]; P = .027), as was distant PFS (median, 13.9 months [95% CI, 12.2 to 16.8] v 11.5 months [95% CI, 10.4 to 12.9]; HR, 0.74 [95% CI, 0.57 to 0.96]; P = .022). Device-related skin adverse events (AEs) were experienced by 76.3% of patients. Most device-related skin AEs were mild to moderate, with 7.7% of patients reporting a grade 3 AE. CONCLUSION: This study demonstrated significant OS, pain-free survival, and distant PFS benefits for TTFields with gemcitabine/nab-paclitaxel versus gemcitabine/nab-paclitaxel in patients with unresectable LA-PAC, with no additive systemic toxicity.
Keywords: dospělí; Female; Adult; ženské pohlaví; Deoxycytidine; doba přežití bez progrese choroby; Pancreatic Neoplasms; gemcitabin; lidé; nádory slinivky břišní; Albumins; Aged, 80 and over; Antineoplastic Combined Chemotherapy Protocols; Paclitaxel; protokoly protinádorové kombinované chemoterapie; deoxycytidin; albuminy; Adenocarcinoma; Male; Aged; Gemcitabine; adenokarcinom; paclitaxel; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; Progression-Free Survival; Middle Aged; Humans